The gut-brain-metabolic axis: exploring the role of microbiota in insulin resistance and cognitive function - Abildinova, Gulshara Zh; Benberin, Valeriy V.; Vochshenkova, Tamara A.; Afshar, Alireza; Mussin, Nadiar M.; Kaliyev, Asset A.; Zhussupova, Zhanna; Tamadon, Amin (Frontiers in Microbiology, 2024)
The gut-brain-metabolic axis has emerged as a critical area of research, highlighting the intricate connections between the gut microbiome, metabolic processes, and cognitive function. This review article delves into the complex interplay between these interconnected systems, exploring their role in the development of insulin resistance and cognitive decline. The article emphasizes the pivotal influence of the gut microbiota on central nervous system (CNS) function, demonstrating how microbial colonization can program the hypothalamic–pituitary–adrenal (HPA) axis for stress response in mice. It further elucidates the mechanisms by which gut microbial carbohydrate metabolism contributes to insulin resistance, a key factor in the pathogenesis of metabolic disorders and cognitive impairment. Notably, the review highlights the therapeutic potential of targeting the gut-brain-metabolic axis through various interventions, such as dietary modifications, probiotics, prebiotics, and fecal microbiota transplantation (FMT). These approaches have shown promising results in improving insulin sensitivity and cognitive function in both animal models and human studies. The article also emphasizes the need for further research to elucidate the specific microbial species and metabolites involved in modulating the gut-brain axis, as well as the long-term effects and safety of these therapeutic interventions. Advances in metagenomics, metabolomics, and bioinformatics are expected to provide deeper insights into the complex interactions within the gut microbiota and their impact on host health. Overall, this comprehensive review underscores the significance of the gut-brain-metabolic axis in the pathogenesis and treatment of metabolic and cognitive disorders, offering a promising avenue for the development of novel therapeutic strategies targeting this intricate system.